Spatial disparities and dynamics in the high quality agricultural development in Heilongjiang Province of China - Jingting Yu; Guanghao Wu (Scientific Reports)
Abstract As a key commodity and strategic reserve grain base in China, evaluating and analyzing the high-quality agricultural development (HQAD) within Heilongjiang Province is crucial for advancing national agricultural quality. We construct a multidimensional evaluation framework with 19 indicators across four dimensions: green agriculture, quality and efficiency improvement of supply, agricultural structural coordination, and shared benefits of development. Using the Entropy Weighted-TOPSIS model, Dagum’s Gini Coefficient, and the Markov chain, the study quantifies the HQAD in Heilongjiang from 2013 to 2022, examining regional disparities and development dynamics. The findings indicate that: (1) Heilongjiang’s overall HQAD has steadily improved, rising from 0.160 in 2013 to 0.396 in 2022, with an annual average growth rate of 10.595%. Agricultural structural coordination, growing at 2.160% annually, has become the primary constraint. (2) Spatial imbalances are evident. The 12 prefecture-level cities in the province are grouped into four regions based on agricultural endowments. Harbin and Qiqihar in the Songnen Plain, and Mudanjiang in the Mudanjiang Semi-mountainous Areas lead in HQAD, while cities in the Sanjiang Plain lag behind. Intra-regional disparities are narrowing in Sanjiang Plain and Xing’an Mountains Regions except the Songnen Plain (from 0.000 to 0.062 during 2013–2022), increasingly contributing to the overall disparity (from 15.717% to 30.065% during 2013–2022). Inter-regional disparities are decreasing, with their contribution declining from 80.769% in 2013 to 37.481% in 2022. (3) HQAD levels in cities exhibit low mobility, fluctuating between medium-low (57.993%) and medium-high (22.082%). Based on these findings, we recommend strengthening agricultural structural coordination, promoting coordinated HQAD tailored to local conditions, and pursing institutional breakthroughs.